Strong divergent selection at multiple loci in two closely related species of ragworts adapted to high and low elevations on Mount Etna - Osborne, OG; Papadopulos, AST; Bridle, JR; Nevado, B; Hiscock, SJ; Filatov, DA (Wiley, 2019)
Recently diverged species present particularly informative systems for studying speciation and maintenance of genetic divergence in the face of gene flow. We investigated speciation in two closely related Senecio species, S. aethnensis and S. chrysanthemifolius, which grow at high and low elevations, respectively, on Mount Etna, Sicily and form a hybrid zone at intermediate elevations. We used a newly generated genome‐wide single nucleotide polymorphism (SNP) dataset from 192 individuals collected over 18 localities along an elevational gradient to reconstruct the likely history of speciation, identify highly differentiated SNPs, and estimate the strength of divergent selection. We found that speciation in this system involved heterogeneous and bidirectional gene flow along the genome, and species experienced marked population size changes in the past. Furthermore, we identified highly‐differentiated SNPs between the species, some of which are located in genes potentially involved in ecological differences between species (such as photosynthesis and UV response). We analysed the shape of these SNPs’ allele frequency clines along the elevational gradient. These clines show significantly variable coincidence and concordance, indicative of the presence of multifarious selective forces. Selection against hybrids is estimated to be very strong (0.16 – 0.78) and one of the highest reported in literature. The combination of strong cumulative selection across the genome and previously identified intrinsic incompatibilities likely work together to maintain the genetic and phenotypic differentiation between these species – pointing to the importance of considering both intrinsic and extrinsic factors when studying divergence and speciation.